Predlagane spremembe ustave - Diskrecija pri izbiranju pobud in ustavnih pritožb za obravnavanje in privilegirani predlagatelji - Sovdat, Jadranka (Dignitas (Ljubljana), 2010)
Insisting on the quantitative approach to the protection of constitutionality,as well as of human rights and fundamental freedoms before the Constitutional Court, which decides several thousand cases a year, contributes little to the quality of this protection and even less to raising its level. Judicial management measures adopted over the last ten years demonstrate the necessity of this approach to ensure work efficiency, however,its scope is limited. For almost twenty years now, the judiciary has also been vested with the task of protecting constitutionality bestowed upon it by the Constitution. If regular courts do not perform this task, nine constitutional judges cannot do it instead of them. The amendments to the Constitution are necessary and so is discretion in selecting which constitutional complaints and petitions the Constitutional Court will decide. The Constitutional Court is committed to adopt clear, unambiguous positions on the contents of human rights and thus create constitutional guidelines to be followed by the regular courts and other state authorities which determine the rights, obligations and legal interests of individuals and legal entities.The introduction of discretion in case selection is closely connected with the scope of privileged applicants auhorised to institute the proceedings for the review of constitutionality of legal acts; if this scope is too broad - as it is now - the introduction of discretion will not achieve the desired effect.
Keywords: pristojnosti; ustavna sodišča; ustavne spremembe; Ustavno sodišče